A transversalidade entre as cidades sustentáveis e as cidades participativas no Brasil - Valicente, Raiana Rassi (Universidade Federal de São Carlos, 2023)
The study of the transversality between sustainable cities and participatory cities is current and necessary because Brazilian urbanization was not planned and thus caused a negative impact on the population, when it should be an organized, systemic movement, thought in a sustainable and participatory way, led by citizens. Brazil, despite being the first country in the world to enact the right to the city, there are major challenges for this right to also embrace and materialize sustainable and participatory cities. This dissertation covers Environmental Sciences, Constitutional, Environmental and Urban Law, aiming to clarify possible indicators and characteristics that make cities have this classification, encompassing themes that impact the quality of life, people's well-being, democratic management and the protagonism of Brazilian citizens. The research was developed from the quali-quantitative method, through documentary and bibliographical research, survey analysis of legal and non-legal norms, books, national and international periodicals, official websites such as well as of the city halls, of the Munic-IBGE. The cities, considered sustainable by the Sustainable Cities of Brazil Program (2021), were analyzed, and also their main characteristics such as geographic location, administrative region, as well as current data such as population, GDP, education, HDI, through a qualitative method, identifying possible grouping by federative union, administrative region, number of inhabitants and if they had an identity profile. Next, it was analyzed whether the 20 Brazilian cities with the best sustainability performances (PCS, 2021) can also be considered participatory, through data such as the existence of a municipal environmental council and the holding of public hearings to involve citizen participation. The results showed that the 20 most sustainable cities in Brazil are located in the State of São Paulo, GDP above the national average, high schooling and 70% of them have a population below 20 thousand inhabitants and are concentrated in the Administrative Region of Campinas/SP. From the point of view of citizen participation, it was found that all of them have a deliberative municipal environmental council, which hold public, face-to-face and virtual hearings. It is inferred that although public participation does not presuppose sustainability, it provides a safe and democratic space for ideas and public policies, which can be focused on sustainability if its population would desire, looks forward to and participates. It is concluded that there are sustainable city indicators that reinforce the importance of providing participatory tools and instruments to its citizens
The transversality between sustainable cities and participatory cities in Brazil
La transversalidad entre ciudades sostenibles y ciudades participativas en Brasil
Keywords: Cidades sustentáveis; Cidades participativas; Gestão democrática das cidades; Sustentabilidade; Participação cidadã; Sustainable cities; Participatory cities; Democratic management of cities; Sustainability; Citizen participation; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::FUNDAMENTOS DE ARQUITETURA E URBANISMO; CIENCIAS SOCIAIS APLICADAS::DIREITO; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITO PUBLICO::DIREITO CONSTITUCIONAL